Testing the potential of auto/biographical life history. (14th November 2016) - Downs, Yvonne
Abstract : Purpose: The purpose of this paper is to describe a methodological experiment designed to test the potential of an auto/biographical (Stanley, 1992) life history. Could it serve a purpose for which it was not originally intended? Specifically, I consider the extent to which a life history articulates with the literature on migration, even though it was not written for this purpose. Design/methodology/approach: I consider this issue via a series of four narrative vignettes representing the story of this experiment. Findings: I found that the life history does more than articulate with the migration literature on conceptual distinction. It also animates, supplements and interrogates theories therein about the utility and futility of making distinctions. In this respect the experiment has been a success. Research limitations/implications: This paper has not explicitly engaged with the ethics and politics of employing life history in ways for which it was not intended. Originality/value: This paper is making a methodological contribution to the area of qualitative research and suggests that multiple analyses might perhaps make life history more attractive to funders.